Influence use Media Learning Videoscribe to Results Study Students of SMPN 2 Rappang - Anwar; Usman M; Nurzin R Kasau; Syamsunir; Sam Hermansyah (MultiTech Publisher, 2023)
The purposes of this research are to investigate:1) The differences in students learning outcomes between taught Videoscribe media and learning without Videoscribe media in class IX SMPN 2 Rappang. On chemical bonding materials 2) The influence of learning with Videoscribe media the learning outcomes in class IX SMPN 2 Rappang on chemical bonding material. The form of the research was quasy experiment with nonequivalent control group design. Sample selection technique was random sampling. The instrument of the research was of test. To find out the differences in student learning outcomes used the U-Mann Whitney test, based on the results of the hypothesis test obtained the value of Asymp. Sig. (2-tailed) of 0.033, the test results showed that there was a differences between students learning outcomes taught Videoscribe media and students learning outcomes taught without Videoscribe. Learning using Videoscribe learning media in class IX SMPN 2 Rappang on chemical bonding material giving the influence of 19.85% toward student learning outcomes.